Konsistensi Perencanaan Pembangunan Daerah Dengan Anggaran Daerah - Sugiarto, Agus; Mutiarin, Dyah (Journal of Governance and Public Policy, 2017)
Development in Indonesia so far has achieved planning approach. Based on Law No. 17 Year 2003 on State FinanceRegional Budget that contained in the budget based on the RKPD, and the mandate of Law Number 25 Year 2004 onNational Development Planning System, states that the planning process should be through participatory musrenbang.The planning process in Gunung Kidul Regency musrenbang promote participatory, although it has been difficult torealize the consistency, and the problems in the development gaps between regions. This thesis examines theconsistency of the results musrenbang on RKPD, until the budget to determine the success of the planning andbudgeting areas of physical infrastructure in the 2013-2015 fiscal year Gunung Kidul Regency, Yogyakarta SpecialProvince and the factors that affect consistency. This research was conducted at 3 SKPD that administer physical andinfrastructure fields. Research using qualitative approach with case study method in which the collection of data,information, through interviews and direct observation in the field related to the planning begin planning meetings,RKPD, until the budget. Observations researchers carried out by conducting direct observation to the field in obtainingdata relevant to the problems of researchers, while the sampling technique used is the technique of non-probabilitysampling with purposive sampling and analysis techniques used triangulation to test the validity of the data by utilizingresearchers with data sources either through the primary data key. The level of consistency during the three years of2013, 2014, 2015 on the physical plane and infrastructure SKPD DPU showed no increase in the year 2013 by 77%, in2014 by 82%, and 96% in 2015. The level of consistency in the SKPD Dishubkominfo 2013 to 2015 is getting better isevidenced in 2013 by 83%, in 2014 by 88%, and in 2015 amounted to 94%. The level of consistency in the SKPDKapedal from 2013 to 2015 have shown improved in 2013 by 88%, in 2014 by 88%, in 2015 by 100%.Perencananaan consistency with the regional development budgets in areas that span the 'hierarchy RKPD, KUA andGunung Kidul district budget of the year 2013-2015 in the field of physical and infrastructure DPU SKPD, Dishubkominfo,and Kapedal for three years tend to rise. Factors that influence the consistency is understanding between SKPD, TAPD;their central policy; the results of the evaluation budgets by the governor; and terwadahinya basic thoughts ofParliament to the program of activities on education.